Enhancing Pronunciation Through Storytelling: A Case Study of Two EFL Learners - Nuraini, Nuraini; Syuhada, Putri; Seri, Ermyna (Talenta Publisher, 2025)
This study aims to investigate the effect of storytelling on pronunciation development among SMP and SMA students. The research focuses on how meaningful repetition, emotional engagement, and confidence-building in stories support articulation, intonation, stress, and rhythm. Using a qualitative approach, students’ storytelling performances were recorded, analyzed, and observed to identify patterns of pronunciation improvement. The results show that repeated phrases in narratives helped students master challenging sounds naturally, emotional content improved prosody and expression, and engaging stories enhanced speaking confidence. Storytelling created authentic, motivating contexts that encouraged students to practice language purposefully, combining cognitive, emotional, and social engagement. These results suggest that storytelling is a dynamic, student-centered strategy for pronunciation teaching, offering repeated practice, emotional engagement, and confidence support simultaneously. Incorporating storytelling into language instruction can improve students’ oral proficiency, prosody, and communicative effectiveness, making pronunciation learning more natural, effective, and enjoyable.